Current status and influencing factors of medication behavior among children and adolescents: a cross-sectional study in China - Sun, Ximu; Yang, Lijie; Han, Qin; Sun, Yixin; Zhou, Han; Xu, Xiaolin; Guo, Peng (Frontiers in Public Health, 2025)
BackgroundChildren face higher medication risks than adults, making safe and rational drug use a societal concern. For children aged 8 and older, early intervention is key to fostering responsible medication habits. This study, grounded in Temporal Self-Regulation Theory (TST), suggests that temporal valuations, behavioral prepotency, and self-regulatory capacity influence medication behaviors, with weaker self-regulation potentially linked to stronger behavioral prepotency.AimsThis study examined medication behavior patterns among Chinese children and adolescents, identified the factors influencing these behaviors, and evaluated the applicability of the TST in elucidating medication behavior.MethodsThis study surveyed 4,288 children and adolescents aged 8–18 from October 2023 to May 2024, recruited from children’s hospitals in 18 cities across mainland China. Data on demographics, health literacy, medication self-efficacy, perceived stress, and medication behavior were collected via questionnaires. Single-factor and multiple linear regression analyses identified significant factors and their contributions to the outcome.ResultsA total of 4,044 questionnaires were collected. The sample included 53.07% males and 46.93% females, with a mean age of 13.60 ± 2.85 years. The mean scores of medication behavior, medication literacy, perceived stress, and medication self-efficacy were 109.49 ± 17.57, 36.00 ± 9.86, 6.55 ± 2.82, 9.24 ± 4.12, respectively. Medication behavior correlated positively with medication literacy (r = 0.420, p < 0.001) and negatively with perceived stress (r = −0.299, p < 0.001) and medication self-efficacy (r = −0.403, p < 0.001). Self-efficacy was measured using reverse-scored items, with lower scores corresponded to higher levels of self-efficacy. Multiple linear regression analysis identified age (β = 0.093, p < 0.001), gender (β = −0.058, p < 0.001), residence within the past 3 months (β = 0.043, p = 0.004), having a separate room (β = 0.027, p = 0.039), medication literacy (β = 0.259, p < 0.001), perceived stress (β = −0.214, p < 0.001), and medication self-efficacy (β = −0.238, p < 0.001) as significant predictors of medication behavior.ConclusionThe study emphasizes that perceived stress, medication literacy, and self-efficacy significantly influence medication behavior in children and adolescents. Targeted interventions in stress management, literacy improvement, and self-efficacy enhancement could foster safer medication use, warranting further research for development and testing.